PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM BANK SAMPAH SEBAGAI UPAYA PENINGKATAN KESADARAN PENGELOLAAN SAMPAH DI DESA KEDUNG PENGAWAS KECAMATAN BABELAN KABUPATEN BEKASI - Panji Maulana; Matdio Siahaan, Kesya Helga Elfareta, Astrid Fitriani, Ernita Sari Maulitna, Rohman Nadiansyah, Rezk (Adiba Aisha Amira, 2026)
Household waste remains an environmental challenge faced by many regions, including Kedung Pengawas Village, Babelan Subdistrict, Bekasi Regency. Low community awareness of waste separation and management has led to an increase in waste generation with potential negative impacts on the environment. This community service activity aims to raise public awareness about the importance of waste management through a community-based waste bank empowerment program. The methods used include field observation, problem identification, program planning, implementation of activities, and evaluation. The program was carried out by establishing waste bank facilities on June 7, 2026, and conducting outreach and education on waste management on June 13, 2026, involving 14 students from Universitas Bhayangkara Jakarta Raya's Community Service Program (Kuliah Kerja Nyata). The results indicate that the waste bank program was able to improve the community's understanding of the importance of waste separation, household waste management, and the utilization of waste with economic value. The community's enthusiasm and participation during the activities demonstrate increased environmental awareness and readiness to support more sustainable waste management. This program is a first step toward encouraging community participation in community-based environmental management and supporting a cleaner, healthier environment in Kedung Pengawas Village.